INNOVATIVE TECHNOLOGIES FOR THE FORMATION OF CONCEPTS OF ENVIRONMENTAL SAFETY IN PRIMARY SCHOOL STUDENTS ON THE BASIS OF AN INTEGRATED APPROACH - Musurmonova, Sh.I. (ILIM hám JÁMIYET, 2022)
The article gives an idea of innovation, innovation technology, innovation processes that can be used in the lessons of the scientist around us, as well as the activity of the reader in the lesson process.